L’implantation de programmes d’insertion professionnelle dans l’enseignement : qu’en pensent les enseignants débutants ? - Joséphine Mukamurera; Maurice Tardif; Aline Niyubahwe; Sawsen Lakhal (Recherches en Éducation)
The education milieu has long left novice teachers for themselves, without support to help them overcome the challenges and difficulties of the early years of teaching. However, a significant institutional change is taking place in North America and in OECD countries through the introduction of induction programs for beginning teachers. In Quebec, nearly 60 % of school boards offer an induction program and, since 2011, the government has allocated increasing financial support, and expects these programs to be implanted in all school environments. However, we do not know how do novice teachers welcome these changes and how do they position themselves with regard to the implementation of induction programs. Our goal is to describe and understand the relationship of novice teachers with regard to the implementation of induction programs intended for them. The study is based on a multidimensional approach to professional integration. The data are drawn from a survey (250 respondents) and semi-structured interviews with 32 novice teachers. The results show that novice teachers support very strongly the implementation of induction programs in schools, but raise some concerns and fears that could affect their participation and the effectiveness of such programs. Some reflection for a successful implementation of induction programs are suggested.